EPIZOOTIC SITUATION ON INFECTIOUS AVIAN DISEASES BASED ON ANALYSIS OF DATA FROM VETERINARY REPORTS - A. N. Spiridonov; O. N. Petrova; V. N. Irza; A. K. Karaulov; V. V. Nikoforovs (Ветеринария сегодня)
The paper covers analysis of data from veterinary reports of the Russian Federation on infectious avian diseases for 2009-2014. The disease rating demonstrates that bacterial diseases are more frequently reported on commercial poultry farms, unlike infectious diseases posing latent risks. Based on the data analysis for avian infectious diseases, it is concluded that vaccine prophylaxis is just one of the tools for control of infectious diseases, but it does not guarantee the virus will stop circulating in the population of susceptible birds or the disease will be eradicated. Timely preventive measures ensuring biosafety help to mitigate the risks of emerging infectious diseases.